Non Traumatic Coma in the Intensive Care Unit: Etiology and Prognosis - Kafle, D. R.; Sah, R. P.; Karki, D. R. (Kathmandu University Medical Journal, 2021)
Background Impaired consciousness and coma is common reason for admission into the intensive care unit .It results from many etiological factors with varying outcome. Causes may vary in different parts of the world as is the outcome depending on the availability of appropriate care to deal with those patients. Objective To identify the etiological factors responsible for non traumatic coma and also evaluate if those factors influence the prognosis. Method This is a hospital based cross sectional study carried out at Nobel Medical College, Biratnagar between December 2019 and December 2020. All the patients who were admitted into the intensive care unit with coma due to non traumatic causes were included in the study. Result One hundred seven patients were enrolled in the study with mean age of the patient 54.5±19 years. There were 61(57%) male. Forty seven (43.9%) patients died while 60(56.1%) patients survived. Common etiological factors identified were impaired renal function 32(29.9%), anoxia 30 (28%), sepsis 28(26.2%), stroke 26(24.3%), metabolic derangement 21(19.6%). Coma due to sepsis was significantly associated with mortality (p=0.001) as was impaired renal function (p =0.035), cardiac disease (p=0.016) and low Glasgow Coma Scale (p=0.046). We did not find any association between age (p=0.53), gender (p=0.94) duration of coma (p=0.75) and mortality. Conclusion Impaired consciousness is a common problem encountered in the intensive care unit with very high mortality. Low Glasgow Coma Scale, Sepsis, impaired renal function and cardiac disease were associated with higher mortality.